2012
DOI: 10.1186/1749-8104-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic targeting of pial surface neural progenitors and immature neurons by neonatal electroporation

Abstract: BackgroundRecent findings have indicated the presence of a progenitor domain at the marginal zone/layer 1 of the cerebral cortex, and it has been suggested that these progenitors have neurogenic and gliogenic potential. However, their contribution to the histogenesis of the cortex remains poorly understood due to difficulties associated with genetically manipulating these unique cells in a population-specific manner.ResultsWe have adapted the electroporation technique to target pial surface cells for rapid gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
2
32
2
Order By: Relevance
“…Interestingly, Tamura and colleagues found that a subpopulation of NG2 þ /DCX þ (doublecortin) cells resides in the rat neocortex, some of which could acquire neuronal specification (Tamura et al 2007). Neuronal progenitors have also been described in cortical layer 1 of neonatal (Breunig et al 2012) as well as adult rats (Ohira et al 2010), wherein they increase 1.6-fold after mild ischemia. No clear evidence of spontaneous neurogenesis has been shown in the intact mouse (as opposed to rat) cerebral cortex, thus confirming the importance of the animal species in parenchymal neurogenesis (see Table 1) and the possible differences existing in cortical structural plasticity when comparing rats and mice.…”
Section: Parenchymal Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Tamura and colleagues found that a subpopulation of NG2 þ /DCX þ (doublecortin) cells resides in the rat neocortex, some of which could acquire neuronal specification (Tamura et al 2007). Neuronal progenitors have also been described in cortical layer 1 of neonatal (Breunig et al 2012) as well as adult rats (Ohira et al 2010), wherein they increase 1.6-fold after mild ischemia. No clear evidence of spontaneous neurogenesis has been shown in the intact mouse (as opposed to rat) cerebral cortex, thus confirming the importance of the animal species in parenchymal neurogenesis (see Table 1) and the possible differences existing in cortical structural plasticity when comparing rats and mice.…”
Section: Parenchymal Neurogenesismentioning
confidence: 99%
“…To further complicate the picture is the existence of glial progenitors retaining proliferative capacity in wide areas of the mature CNS (reviewed in Dawson et al 2000;Butt et al 2005;Nishiyama et al 2009;Trotter et al 2010). The largest class of these cells express NG2 (Horner et al 2000) and are often referred to simply as NG2 cells.…”
Section: Progenitors Involved In Noncanonical Neurogenic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In large part, this has been due to the development of increasingly precise genetic tools, such as nervous system specific Cre recombination of floxed alleles or retroviral lineage tracing 4 . However, one progenitor region-the pial surface progenitor zone-has only recently been described in any detail [5][6][7] and awaits comprehensive examination.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult brain, it has been reported that interneurons can be born from pial surface progenitors following hypoxic challenge 7 . However, the contribution of this region to his to genensis during embryonic and postnatal development has remained obscure in part due to the difficulty of specifically investigating this region 6 . In the superior colliculus and in the cerebral cortex, superficial (or layer I in the cortex) interneurons may modulate the circuit output of underlying excitatory neuron populations and thus contribute significantly to the function of these structures.…”
Section: Introductionmentioning
confidence: 99%